KAJIAN HUKUM ISLAM DAN UNDANG-UNDANG PERLINDUNGAN ANAK TERHADAP PERAN ORANG TUA KARIER DALAM MENGASUH ANAK DISABILITAS - Qurrotun Nikmah; Lukman Hakim; Abdul Aziz (AL-ASHLAH : Jurnal Hukum Keluarga dan Hukum Islam, 2025)
The dynamics of career-oriented families in the modern era have brought significant changes to parenting patterns, including for children with disabilities. Dual-income parents often face challenges in optimally fulfilling the physical, emotional, and educational needs of their children. This study aims to analyze the parenting roles of working parents towards children with disabilities in career-oriented families from the perspectives of Islamic law and child protection legislation. The research employs an empirical approach with a descriptive-qualitative method. Data were collected through interviews and observations involving five families in Barurejo Village, Siliragung Subdistrict, Banyuwangi Regency. The research findings indicate that although both parents are employed, they must still fulfill their parenting responsibilities holistically through role-sharing, time adjustment, and support for the child's therapy. From the perspective of Islamic law, parenting emphasizes the principles of maÃ¡Â¹Â£laÃ¡Â¸Â¥ah al-maÃ¡Â¸Â¥Ã¡Â¸ÂÃ…Â«n and maqÃ„ÂÃ¡Â¹Â£id al-sharÃ„Â«Ã¢â‚¬Ëœah. In contrast, positive law guarantees the rights of children with disabilities through Law Number 35 of 2014 and Law Number 8 of 2016. The study concludes that the active involvement of both parents is pivotal to the success of caring for children with disabilities and can be implemented adaptively, provided it is grounded in the child's best interests.